Concomitant use of renin-angiotensin system inhibitors augments the efficacy of immune checkpoint inhibitors: a systematic review and meta-analysis - Yu, Junjie; Meng, Fangang; Sui, Wenxia; Yu, Junmin; Shen, Jinhai (Frontiers in Pharmacology, 2024)
The impact of renin-angiotensin system inhibitors (RASIs) on the outcome of hypertensive cancer patients undergoing immune checkpoint inhibitor (ICIs) therapy remains ambiguous. This investigation sought to elucidate the consequences of RASIs use on the prognosis for this specific patient group within the context of ICIs treatment, aspiring to provide a clearer basis for rational, evidence-driven choices in the clinical prescription of these medications.A comprehensive search was conducted on PubMed, Embase, Web of Science, and the Cochrane Library for original studies published up to August 6, 2023. Studies published in English reporting hazard ratios (HRs) with 95% confidence intervals (CIs) for overall survival (OS) and/or progression-free survival (PFS) were included. All statistical analyses were executed utilizing R software (version 4.2.2).Results: A total of 13 studies, encompassing approximately 12,595 patients, satisfied the inclusion criteria. Meta-analyses demonstrated a statistically significant association between the use of RASIs and a favorable outcome in OS (HR, 0.74; 95%CI, 0.62-0.88) and PFS (HR, 0.77; 95%CI, 0.62-0.96) among cancer patients receiving ICIs treatment.This investigation provides compelling evidence supporting the beneficial prognostic impact of RASIs on cancer patients receiving ICIs. RASIs present a viable option as antihypertensive agents for cancer patients with hypertension undergoing ICIs treatment. Further exploration and validation through prospective studies are necessary to establish definitive guidelines for the use of RASIs in managing hypertensive cancer patients undergoing immunotherapy with ICIs